Release of ATP by TRPV4 activation is dependent upon the expression of AQP2 in renal cells. Issue 4 (17th August 2020) - Pizzoni, Alejandro; Bazzi, Zaher; Di Giusto, Gisela; Alvarez, Cora L.; Rivarola, Valeria; Capurro, Claudia; Schwarzbaum, Pablo J.; Ford, Paula
Abstract: Increasing evidence indicates that aquaporins (AQPs) exert an influence in cell signaling by the interplay with the transient receptor potential vanilloid 4 (TRPV4) channel. We previously found that TRPV4 physically and functionally interacts with AQP2 in cortical collecting ducts (CCD) cells, favoring cell volume regulation and cell migration. Because TRPV4 was implicated in ATP release in several tissues, we investigated the possibility that TRPV4/AQP2 interaction influences ATP release in CCD cells. Using two CCD cell lines expressing or not AQP2, we measured extracellular ATP (ATPe) under TRPV4 activation and intracellular Ca 2+ under ATP addition. We found that AQP2 is critical for the release of ATP induced by TRPV4 activation. This ATP release occurs by an exocytic and a conductive route. ATPe, in turn, stimulates purinergic receptors leading to ATPe‐induced ATP release by a Ca 2+ ‐dependent mechanism. We propose that AQP2 by modulating Ca 2+ and ATP differently could explain AQP2‐increased cell migration. Abstract : Aquaporin‐2 (AQP2) is critical for the release of ATP induced by transient receptor potential vanilloid 4 (TRPV4) activation. This ATP release occurs by an exocytic and a conductive route. Extracellular ATP (ATPe), in turn, stimulates purinergic receptors leading to ATPe‐induced ATP release by a Ca 2+ ‐dependent mechanism. We propose that AQP2 by modulating Ca 2+ and ATP differently could explain AQP2‐increased cell migration.